The Magical Realism in Makoto Shinkai’s Kimi No Na Wa (Your Name) (2016) - Daffa Pratama Sukoco (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2023)
Magical elements do in fact exist, and their presence cannot be explained by human understanding of the outside world (Srikanth. 2014: 331). It is thought that magical realism blurs the distinction between reality and magic by fusing the two concepts into one. Kimi no Na wa (Your Name.) is a CoMix Wave Films anime film directed and written by Makoto Shinkai. It tells the story of two high school students, Mitsuha and Taki. Who one day, they both wake up to find that they have switched bodies. They believe body-swapping is not a coincidence, but rather a consequence of a mysterious event that is connected to their pasts. This research aims to identify the elements of magical realism portrayed in the film, and explore the connections between magical realism to determine the impact of the elements of magical realism on the structure of the film. In this research, the researcher will analyze the elements of magical realism in the movie Kimi no Na wa by Makoto Shinkai, with Wendy B. Faris' five magical realism elements theory. Subtitles and Screenshots from the film Kimi no Na wa are being used by the researcher as data sources. There are also many components that can be considered as elements of magical realism in this movie which are unfortunately rarely discussed in the community. The results of this research found that Makoto Shinkai’s film Kimi no Na wa is categorized as a work of magical realism literature, because it contains 5 characteristics of magical realism. And the significant impact of magical realism elements on the structure of the film is its disruption to the traditional narrative structures.Keywords: Magical, Realism, Magical Realism, Anime, Kimi no Na wa, Makoto Shinkai.